In Search of Alternatives: The Making of Grassroots Politics and Power in Argentina. - SCHAUMBERG, HEIKE (Bulletin of Latin American Research, 2008)
This article analyses ethnographically the reconfigurations of the state and relations of power through their dynamic interactions with subaltern alternatives that emerged in the 2001 uprising in Argentina. In this regard, it counters influential interpretations of these events articulated within John Holloway’s framework of ‘anti-power’, which ignores the reconstruction of the state, and rank and file trade unionism. The article concludes that intensified class and political struggles in the region offer new spaces for contesting hegemonic reinventions of populism and ‘top-down’ socialism in Latin America.